Klein–Gordon Oscillator in a Topologically Nontrivial Space-Time - L. C. N. Santos; C. E. Mota; C. C. Barros (Advances in High Energy Physics)
In this study, we analyze solutions of the wave equation for scalar particles in a space-time with nontrivial topology. Solutions for the Klein–Gordon oscillator are found considering two configurations of this space-time. In the first one, the S1×R3 space is assumed where the metric is written in the usual inertial frame of reference. In the second case, we consider a rotating reference frame adapted to the circle S1. We obtained compact expressions for the energy spectrum and for the particles wave functions in both configurations. Additionally, we show that the energy spectrum of the solution associated with the rotating system has an additional term that breaks the symmetry around E=0.